1998
DOI: 10.1017/s1041610298005468
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid Personality Traits in Alzheimer's Disease: Do They Predispose to Noncognitive Behavioral Symptoms?

Abstract: The purpose of this study was to examine whether premorbid personality traits predispose to noncognitive symptoms in Alzheimer's disease (AD). The Munich Personality Test was used to evaluate caregivers' perception of personality prior to symptom onset in 56 outpatients with probable AD. Caregivers also completed the “mood” and “disturbed behavior” scales of the Nurses' Observation Scale for Geriatric Patients. A neuropsychiatrist rated depressive symptoms on the Cornell Scale for Depression and the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…A number of studies suggest that premorbid personality characteristics may be predictive of BPS in dementia [20,24,25,26,27] while still others reach the opposite conclusion for patients at an early stage of AD [13,40,41]. Some of these characteristics may correspond to an overexpression of premorbid personality traits [11,13,21], but no such studies are available for MCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies suggest that premorbid personality characteristics may be predictive of BPS in dementia [20,24,25,26,27] while still others reach the opposite conclusion for patients at an early stage of AD [13,40,41]. Some of these characteristics may correspond to an overexpression of premorbid personality traits [11,13,21], but no such studies are available for MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Premorbid personality may also favour BPS in later dementia [24,25,26,27], but these links remain unclear due to, among other reasons, the often unclear personality concepts used in different studies. Studies have shown personality changes and BPS in early AD [11,13], but these findings are preliminary and have not been replicated in MCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its effect on depressive symptoms mirrors that in older people without dementia [22] . Premorbid personality factors are known to influence BPSDs [23] . Perhaps NART-IQ reflects a general robustness of the brain (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Premorbid personality problems are also correlated with higher incidence of behavioral disturbances in dementia patients. 18 Specific behaviors such as screaming and vocal outbursts are strongly correlated with increased functional impairment, depressed affect, and social networks of poor quality. [19][20][21] Deutsch and Rovner 22 found that Alzheimer's disease patients who were more physically violent were more dependent on others regarding oral hygiene, dressing, and toilet needs.…”
Section: Predisposing and Precipitating Factorsmentioning
confidence: 99%